2019
DOI: 10.1097/rlu.0000000000002398
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid 11C-MET PET/MRI Combined With “Machine Learning” in Glioma Diagnosis According to the Revised Glioma WHO Classification 2016

Abstract: Purpose With the advent of the revised WHO classification from 2016, molecular features, including isocitrate dehydrogenase (IDH) mutation have become important in glioma subtyping. This pilot trial analyzed the potential for 11C-methionine (MET) PET/MRI in classifying glioma according to the revised WHO classification using a machine learning model. Methods Patients with newly diagnosed WHO grade II–IV glioma underwent preoperative MET-PET/MRI imaging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 16 publications
1
21
0
2
Order By: Relevance
“…PET imaging was suggested to be informative for preoperatively differentiating gliomas according to 2016 WHO classification, particularly for differentiating IDH-wildtype and IDH-mutant tumors ( 19 ). A study of hybrid 11 C-MET PET/MRI imaging including 39 glioma patients described that ROC analysis of TNRmax had a high AUC of 0.79 for predicting IDH status ( 16 ). Another study retrospectively evaluated 109 patients with newly diagnosed glioma also indicated that 11 C-MET uptake was negatively correlated with IDH mutational status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET imaging was suggested to be informative for preoperatively differentiating gliomas according to 2016 WHO classification, particularly for differentiating IDH-wildtype and IDH-mutant tumors ( 19 ). A study of hybrid 11 C-MET PET/MRI imaging including 39 glioma patients described that ROC analysis of TNRmax had a high AUC of 0.79 for predicting IDH status ( 16 ). Another study retrospectively evaluated 109 patients with newly diagnosed glioma also indicated that 11 C-MET uptake was negatively correlated with IDH mutational status.…”
Section: Discussionmentioning
confidence: 99%
“…The results are inspiring since T2-weighted MR imaging is widely available and routinely performed in the assessment of gliomas. Some studies have explored the relationship between amino acid uptake characteristics of gliomas and IDH mutation status (15)(16)(17)(18)(19). We aimed to develop a novel and convenient statistical model that combines PET features and clinical factors for an IDH-predictive signature.…”
Section: Introductionmentioning
confidence: 99%
“…PET images could reveal metabolic differences among gliomas, providing a possible non-invasive preoperative molecular diagnosis with FDG, 11 C-choline(CHO), or 11 C-methionine(MET) [21,22]. MET-PET/MRI has been reported to predict the IDH mutation of gliomas, by calculating the maximum tumor-brain ratio of MET uptake, and the receiver operating characteristic (ROC) analysis showed high AUC of 0.79 [23]. The biological tumor volume of early glioma differs from the standard 20-40 min FDG-PET to determine IDH status [24].…”
Section: Introductionmentioning
confidence: 99%
“…Mittels der Texturanalyse konnte bereits die ärztliche Einschätzung und bildbasierte Charakterisierung des Tu-mors reproduziert werden. Dennoch sind größere Fallgruppen essenziell um diese Methodik zu verbessern sowie auf Basis des guten Kontrasts von Tumor-zu-Hintergrund der gängigen Radiotracer verlässliche semi-maschinelle oder maschinelle Segmentations-Modelle/-Programme zu entwickeln und zu etablieren [1,9].…”
Section: Eine Mögliche Ideale Zukünftige Interaktion Zwischen Menscheunclassified